Processed lateral root of Aconitum carmichaelii Debx.: A review of cardiotonic effects and cardiotoxicity on molecular mechanisms - Jing Zhang; Jing Zhang; Dan Li; Dan Li; Dan Zhong; Qinmei Zhou; Qinmei Zhou; Yanpeng Yin; Yanpeng Yin; Jihai Gao; Jihai Gao; Cheng Peng; et al. (Frontiers Media S.A., 2022)
Fuzi, the lateral root of A. carmichaelii Debx., is a typical traditional herbal medicine with both poisonousness and effectiveness, and often used in the treatment of heart failure and other heart diseases. In this review, we searched domestic and foreign literature to sort out the molecular mechanisms of cardiotonic and cardiotoxicity of Fuzi, also including its components. The major bioactive components of Fuzi for cardiotonic are total alkaloids, polysaccharide and the water-soluble alkaloids, with specific mechanisms manifested in the inhibition of myocardial fibrosis, apoptosis and autophagy, and improvement of mitochondrial energy metabolism, which involves RAAS system, PI3K/AKT, JAK/STAT, AMPK/mTOR signaling pathway, etc. Diester-diterpenoid alkaloids in Fuzi can produce cardiotoxic effects by over-activating Na+ and Ca2+ ion channels, over-activating NLRP3/ASC/caspase-3 inflammatory pathway and mitochondria mediated apoptosis pathway. And three clinically used preparations containing Fuzi are also used as representatives to summarize their cardiac-strengthening molecular mechanisms. To sum up, Fuzi has shown valuable cardiotonic effects due to extensive basic and clinical studies, but its cardiotonic mechanisms have not been systematically sorted out. Therefore, it is a need for deeper investigation in the mechanisms of water-soluble alkaloids with low content but obvious therapeutic effect, as well as polysaccharide.